EGG YOLK COLOR OF COMMERCIAL LAYING HENS RECEIVING COMMERCIAL PIGMENT IN DIET - Fassani, Edison Jose (2019)
The aim of this study was to evaluate the egg yolk pigmentation of laying hens fed commercial powdered products (CPP) based on canthaxanthin and urucum seed oil. A total of 240 commercial laying hens at 55 weeks of age were used, which received five different rations: control (CR) based on corn and soybean meal, CR with two levels (70 and 140 ppm) of CPP and CR with two levels of mixture between synthetic commercial pigments Carophyll® Yellow and Red (20 + 10 ppm) and (15 + 30 ppm), and four replicates of twelve birds each. The performance and color of the yolk were evaluated, using the colorimetric fan. There was no effect on the performance of the laying hens, except for the color of the yolk, which showed interaction of the pigmentants in the different periods. At seven days of supply there was stabilization of pigmentation with use of 70 ppm of the commercial powdered product, while egg yolks from hens receiving the inclusion of 140 ppm stabilized color at 14 days of delivery. The commercial product based on canthaxanthin and urucum seed oil is efficient in egg yolk pigmentation in yellow maize based diets.Keywords: Additives; Poultry; Carotenoids; Natural pigmentation; Egg production.